Mujeres en rebelión. Una mirada desde el diario de Francisco Tadeo Diez de Medina ( 1781) - Mendieta, Pilar (2005)
The article get downs the important role of indigenous women in the rebellion led by Tupac Katari in 1781 against the Spanish rule. The article is supported with the diary or «oidor» Francisco Tadeo Diez de Medina which provides thought-provoking comments about the participation of indigenous women, especially of Gregoria Apaza and Katari’s sister and wife, Bartolina Sisa. The article is mainly aimed at shedding light on the relevance of the ethnic-cultural and gender dimensions underlying the rebellion.